2019
DOI: 10.3390/nu11061234
|View full text |Cite
|
Sign up to set email alerts
|

Early Time-Restricted Feeding Improves 24-Hour Glucose Levels and Affects Markers of the Circadian Clock, Aging, and Autophagy in Humans

Abstract: Time-restricted feeding (TRF) is a form of intermittent fasting that involves having a longer daily fasting period. Preliminary studies report that TRF improves cardiometabolic health in rodents and humans. Here, we performed the first study to determine how TRF affects gene expression, circulating hormones, and diurnal patterns in cardiometabolic risk factors in humans. Eleven overweight adults participated in a 4-day randomized crossover study where they ate between 8 am and 2 pm (early TRF (eTRF)) and betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
472
4
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 432 publications
(574 citation statements)
references
References 69 publications
16
472
4
8
Order By: Relevance
“…Advances in Geriatric Medicine and Research 18 of 32 the macronutrient to restrict during CR or IF in order to promote fatty acid and ketone oxidation. However, in the studies discussed in this paper, carbohydrate intake was between that of a normal Western diet, ~45-60% of daily energy intake, during CR and IF periods [22,166,167,169,185,[194][195][196]. Daily protein intake, on the other hand, was kept under ~15% of daily kcals.…”
Section: Macronutrient Considerations For Calorie Restrictionmentioning
confidence: 99%
See 2 more Smart Citations
“…Advances in Geriatric Medicine and Research 18 of 32 the macronutrient to restrict during CR or IF in order to promote fatty acid and ketone oxidation. However, in the studies discussed in this paper, carbohydrate intake was between that of a normal Western diet, ~45-60% of daily energy intake, during CR and IF periods [22,166,167,169,185,[194][195][196]. Daily protein intake, on the other hand, was kept under ~15% of daily kcals.…”
Section: Macronutrient Considerations For Calorie Restrictionmentioning
confidence: 99%
“…Alternatively, IF involves frequent, short-duration CR such as "5:2 fasting", alternate day fasting, periodic fasting, and daily TRF, all which are capable of producing health benefits comparable to that of CR [183][184][185]. The 5:2 fasting protocol involves ad libitum feeding 5-days per week with 2-days of severe CR (i.e., 500 kcals/day) or complete cessation of caloric intake (i.e., 24-h fast) on non-consecutive days [179,183].…”
Section: Restriction Of Calories Augments Autophagymentioning
confidence: 99%
See 1 more Smart Citation
“…The study demonstrated that early TRF (6-h feeding period, with dinner before 3 p.m.) led to reduced blood pressure, oxidative stress, and appetite, and increased insulin sensitivity and β cell responsiveness compared to the controls (12-h feeding period) for 5 weeks (28). Another two recent studies assessed the effect of early TRF (08:00-14:00) vs. a control protocol (08:00-20:00) in a randomized crossover design on 11 overweight adults (28,29). Early TRF significantly reduced the mean 24-h glucose levels and glycemic excursions (29).…”
Section: Mealtime and Cardiometabolic Riskmentioning
confidence: 99%
“…Another two recent studies assessed the effect of early TRF (08:00-14:00) vs. a control protocol (08:00-20:00) in a randomized crossover design on 11 overweight adults (28,29). Early TRF significantly reduced the mean 24-h glucose levels and glycemic excursions (29). Moreover, the early time-feeding protocol led to decreased appetite without affecting energy expenditure (30).…”
Section: Mealtime and Cardiometabolic Riskmentioning
confidence: 99%